Simulation, fabrication and characterization of PMOS transistor device - Yusuf, Siti Idzura (2006)
In a low supply voltage CMOS technology, it is desirable to scale threshold voltage and gate length for improving circuit performance. Therefore, a project has been carried out inside KUiTTHO's microelectronic cleanroom to produce a method that has better l ow power/low voltage current concentrate on p-channel (PMOS). An experiment was also done to determine the right parameter value to b e used for fabrication process such as oxidation process thickness rate, sheet resistance and metal thickness. From the parameter value obtained, 0.3 m m and 0.5 mm PMOS transistor had been successfully produced. Fabrication simulation was performed to produce a 0.1 |am and 0.3p.m PMOS transistor by using the ISE-TCAD software. The trade off between threshold voltage (VTH), gate length (LG) and thin oxide thickness (tox) are discussed to determine the characteristics of the transistors. It shows that for 0.3mm (toX = 860A) PMOS transistor the value of VT H =-3.33V and 0.5 mm ( t ^ = 910A), VT H value =-4.3V. From the simulation result show for 0.1 jim (to* = 200A), VT H = - 0 . 3 1 4V and for 0 . 5 | im (400A) Vt h = -0.634V. The result shows that, with decreasing gate length and oxide thickness will produce lower value of threshold voltage. Minimum value of threshold voltage can result in a better performance of transistor. Another parameter must be taken into consideration such as leakage current, resistivity and conductivity to get a better design of PMOS transistor in future research.